NONCOMMUNICABLE DISEASES PREVALENCE AND HEALTH-POST ATTENDANCE ASSOCIATED FACTORS IN AN URBAN SLUM AND A MIDDLE-INCOME COMMUNITY - Yunisa Astiarani; Kevin Kristian; Nur Fitriah (Berkala Ilmiah Kedokteran Duta Wacana, 2022)
Background Non-communicable Diseases (NCDs) become the leading cause of death, particularly in low-income settings. However, the health post for NCDs called Pos Pembinaan Terpadu (Posbindu) aimed to be the screening post in the community loses its function due to residents’ low visitation.Objective This study aimed to investigate NCD’s prevalence in low-middle income communities and analyzed health-post attendance associated factors in two areas with different socioeconomic backgrounds.Methods A community survey was conducted on a slum and a middle-income hamlet in Pejagalan village. A total of 470 residents aged 15 and above responded to the demographic and NCDs risk factors questionnaire. Logistic regression was performed separately in the two areas.Results The prevalence of NCDs and its multimorbidity are presiding in the slum, while the health-post attendance in the area associated with women visitors (odds ratio [OR]=4.2; 95% confidence interval [CI]=1.9-9.1), the 30-59 age group (OR=5.0; 95%CI=2-10), having no education (OR=4.7; 95%CI=1.9-5.5), unemployed (OR=2.5; 95%CI=1.3-5.7), and practicing a less-fat diet (OR=3.2; 95%CI=1.7-6.0). The elderly were less likely to visit the posts (OR=0.3; 95%CI=0.1-0.9). Meanwhile, increasing age (OR=1.03; 95%CI=1.01-1,05), residents who practice regular physical activity (OR= 2.3; 95% CI=1.3-4.1), and not smoking (OR=2.9; 95%CI=1.4-6.0) were associated with community health-post attendance in middle-income hamlet.Conclusion The results indicated that NCDs prevalence in the slum needs proper attention, particularly in elderly and male residents, due to low visits to the health post. Enhancing the specific target of NCDs screening respective to the areas would be the best effort to prevent further NCDs prevalence.